Immigrants and National Anxieties in 21st-Century Spanish Film - Julia C Barnes (Studies in 20th & 21st Century Literature, 2019)
This article analyzes the ways that gender and race inform the portrayals of native-born Spaniards and immigrants in Flores de otro mundo (Flowers from Another World) (1999), Un novio para Yasmina 'A Fiancé for Yasmina' (2008), Retorno a Hansala (Return to Hansala) (2008), Biutiful (2010) and 15 años + 1 día (Fifteen Years and One Day) (2013). These films position the white Spanish man at the center of their stories, even when they are not the sole protagonists. Immigrant men of color, in contrast, are most frequently portrayed as parasitical, delinquent, and criminal. White Spanish women are portrayed negatively as well, sometimes criminalized, but just as frequently portrayed as modern, liberated women who have rejected their traditional responsibilities as reproducers and caretakers of the nation. This leaves immigrant women of color, whose apparent willingness to fill the void left by white Spanish women grants them a special status as the savior of the Spanish family. Through these repeating themes and types, recent Spanish film acknowledges contemporary anxieties about immigration as well as continuing anxieties due to decreased native demographics.
Keywords: Spain; film; immigration; twenty-first century; Flores de otro mundo; Biutiful; Un novio para Yasmina; Retorno a Hansala; 15 años + un día; Icíar Bollaín; Chus Gutiérrez; Irene Cardona; Alejandro González Iñárritu; Gracia Querejeta